PLURALITY AND UNITY WITHIN INTRARELIGIOUS DISCOURSE - D’Souza, Keith (Journal of Dharma, 2008)
The plural nature of intrareligious discourse and its normative strategies help to preserve as well as set limits to the plurality we experience in our existential situations. By ‘intrareligious’ I mean the discourse prevalent within any given religious tradition, though much of my argumentation could usefully be extrapolated to the field of interreligious discourse as well, i.e., the discourse between persons and communities of different religious traditions. By ‘discourse’ I mean communication comprising of a specific concern, context, orientation, and terminology. The term ‘discourse’ in this study includes not only the cognitive dimensions of religious language, but also affective, existential, practical, and social dimensions of religious communication in general.